2017
DOI: 10.5267/j.uscm.2017.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the critical success factors of automotive engine remanufacturing in India

Abstract: Extension of product's useful life through product recovery options can help to reduce the consumption of natural resource and environmental pollution. Remanufacturing operation is considered as the most suitable product recovery option for automotive parts. The objective of this paper is to identify the barriers and the critical success factors in automotive engine remanufacturing. A case study is carried out in an automotive engine remanufacturing plant, situated in the south-western part of India. In this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As presented in Table 4, Govindan et al [94] identified the uncertainties of production and operations in ELV remanufacturing, which are crucial obstacles in this industry. Besides that, Chakraborty et al [95] investigated the uncertainties of production and operations in engine remanufacturing. Liao et al [96] investigated the uncertainties in engine remanufacturing, specifically uncertainties in relation to customer demand and profit acquisition in terms of quality and quantity.…”
Section: Production and Operationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As presented in Table 4, Govindan et al [94] identified the uncertainties of production and operations in ELV remanufacturing, which are crucial obstacles in this industry. Besides that, Chakraborty et al [95] investigated the uncertainties of production and operations in engine remanufacturing. Liao et al [96] investigated the uncertainties in engine remanufacturing, specifically uncertainties in relation to customer demand and profit acquisition in terms of quality and quantity.…”
Section: Production and Operationsmentioning
confidence: 99%
“…Most of the previous studies adopted quantitative techniques as their uncertainty coping mechanism. Based on the findings in Table 4, several studies used MCDM in their studies and applied methods such as the combination of fuzzy analytical hierarchy process (FAHP) and fuzzy TOPSIS (FTOPSIS) [114], FAHP [103], FTOPSIS [95], the combination of FAHP and fuzzy grey relation analysis and technique for order performance by similarity to ideal solution (G-TOPSIS) [97], the mixed method of interval triangular fuzzy numbers type-2 and modified ELECTRE [104], analytical hierarchy process (AHP) [118], and the combination of data envelopment analysis (DEA), TOPSIS, and ELECTRE [106].…”
Section: Managing Production and Operations Uncertaintymentioning
confidence: 99%
“…Owing to technology innovation and mass industrial production, new products have burgeoned around the world, generating many waste products, and severely affecting the environment [ 1 , 2 , 3 , 4 , 5 ]. Confronting the situation, remanufacturing, which involves a series of processes that restore end-of-life products, parts or components, and returns them back to as-new conditions, has become a global strategy to deal with the massive amount of scrapped products [ 6 , 7 , 8 , 9 ]. The scrapped products processed by remanufacturing are referred as “Remanufactured Products” which can match the same properties and performance of the original ones [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%